MYSTIC POETS OF BHAKTI MOVEMENT - Muttickal, James (Journal of Dharma, 2004)
Bhakti or devotion to God is found in every religion and is considered to be a way to attain God realization. From ancient times onwards bhakti is considered as a way of God-realization along with karma (good actions) and jaana (knowledge). In the medieval period, however, bhakti comes to the forefront as the best means with the writings of mystic poets. In India, this took the shape of big movements with a number of mystics writing their mystical poems in vernaculars. They created lasting imprints in the ethos of Indian mind. Along with it arose the Sufi poets in the Islamic world as the lovers of God, who refused to be bound by the rules and regulations of shariat or orthodox Islam. In Christianity at that time came the mystical poems of St. John of the Cross and the writings of St. Theresa of Avila. In India it revolutionized the concept of religion. With bhakti coming to the forefront the other two ways karma and jaana receded to the background. The ritualistic religion of Brahmanism gave way to new and effective waves of the religion of the "lovers of God" (bhaktas), the membership to which was spread across all classes and castes. This movement swept away the masses with it and God became attainable to ordinary people.